The syntax of intransitive alternations: asymmetries across languages - Mangialavori Rasia, Eugenia (Glossa (London), 2025)
This paper analyzes intransitive alternations in relation to manner/result transitivity patterns. We focus on productivity and distribution in Romance, Greek, and English, where a major asymmetry is created by the (un)availability of monadic alternates featuring a stative cause as the single participant (e.g. Caffeine dehydrates; Covid kills). These constructions are contrasted with intransitive alternatives generally considered in the literature, like the Characteristic Property of Agent Alternation (e.g. This dog bites). Criteria like eventivity, episodicity, agentivity, and intentionality/volitionality are examined. We find that the types contrasted correspond to two structurally distinct kinds of predication. Major differences emerge between originally transitive structures where the object, even if unexpressed/unspecified, is assigned a place in the configuration (the type traditionally explored) vs. original atransitive variants consisting only of the external-argument-licensing head, with consequently different semantic and syntactic properties. This distinction also explains the apparently striking distribution of intransitivity alternations in psych verbs. We note that certain verbs, even if eligible for psych predication like bother or intimidate, can have other uses related to manner-of-behavior predications. We identify central conditions (eventivity, animacy/agenthood, defeasibility) regulating argument/event realization: in languages like English, whereas structurally monadic variants with a cause subject are generally unavailable (*Madrid bewitches/fascinates), manner-type alternatives are fully productive for verbs with non-psych uses, offering less-constrained conditions for object drop/ non-specification. In Romance and Greek, both structures are systematically available, offering distinct syntactic and semantic computations for intransitive variants across different verb classes.